From Classroom to Ideological Space: The Formation of Radicalism in the Academic Environment - Misrah; Nurcahaya; Ismail; Hutagalung, Syahrial Arif (Faculty of Law, Universitas Pekalongan, 2024)
Radicalism remains a significant concern in Indonesia, particularly inside the educational setting. This study seeks to comprehend the phenomena of radicalism among students, particularly among Islamic Religious Universities (PTKI). Data was acquired using a qualitative technique through interviews, observations, focus group discussions, and surveys at five PTKIs in Sumatra. Significant findings indicate that approximately 50% of students acknowledge the presence of radical ideology on their campuses, however their understanding of the term of radicalism varies. Women have been recognized for their roles in radical organizations, serving as both recruiters and logistical supporters. This study's result underscores the necessity for enhanced literacy on radicalism among students, as well as the imperative to elevate understanding of women's participation in radical movements, which necessitates academic and legislative measures to disrupt the cycle of radicalism..